REVIVING ISLAMIC VALUES IN CONTEMPORARY ARAB ARCHITECTURE |CASE STUDY - Alqub, Heba; Mellin, Robert (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2020)
Contemporary architecture in the Arab-Islamic World is facing the challenge of finding a distinctive character that combines both the heritage of the regional building traditions and the modern society lifestyle. Since few apparent attempts aim to articulate an identity for regional architecture, this research investigates the work of the Jordanian architect, Ayman Zuaiter. Their jobs attempt to integrate the cultural values and traditions with the contemporary Arab-Islamic architecture and seek to express and represent the spirit, values, and underlying principles of the regional heritage. This study aims to offer a deeper understanding of design as both method and production, contributing in turn to understanding regional and socio-economic considerations behind forms. This study will be based on the analysis of one of Zuaiter's residential buildings, Al-Tabba'a House. The research method is mainly exploratory, which combines a review of the project primarily in terms of cultural context; responding to the site itself (understanding regional and socio-economic considerations behind forms); concepts and how techniques helped them appear the way they are; multiple personal interviews with the architect aiming to understand his design strategies to revive traditions; and the external influences that affect the design process. This study shows that Islamic Values could be delivered through each design feature in Ayman Zuaiter’s work of contemporary Arab architecture.